2005
DOI: 10.1111/j.1365-2141.2004.05351.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher disease: pathological mechanisms and modern management

Abstract: Summary Gaucher disease, the most common lysosomal storage disorder, is caused by the defective activity of the lysosomal enzyme, acid‐β‐glucosidase (GlcCerase), leading to accumulation of glucosylceramide (GlcCer), particularly in cells of the macrophage lineage. Nearly 200 mutations in GlcCerase have been described, but for the most part, genotype‐phenotype correlations are weak, and little is known about the down‐stream biochemical changes that occur upon GlcCer accumulation that result in cell and tissue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
0
19

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(195 citation statements)
references
References 102 publications
1
175
0
19
Order By: Relevance
“…The breakdown products resulting from the proteolysis may also be atypical and pathogenic; there is evidence that cytoplasmic cathepsin D produces a tau protein fragment comparable to that thought to 'seed' the formation of neurofibrillary tangles Lynch, 1996, 1998), while inhibitors of the enzyme block the development of phosphorylated tau deposits (Bi et al, 2000). Third, metabolism within lysosomes generates products necessary for proper functioning of the endoplasmic reticulum, the loss of which can impair calcium buffering (Jmoudiak and Futerman, 2005). This would have a diverse array of effects including activation of the calcium-sensitive protease calpain (Fig.…”
Section: Relationship Of Plasticity Deficits To Generalized Brain Agingmentioning
confidence: 99%
“…The breakdown products resulting from the proteolysis may also be atypical and pathogenic; there is evidence that cytoplasmic cathepsin D produces a tau protein fragment comparable to that thought to 'seed' the formation of neurofibrillary tangles Lynch, 1996, 1998), while inhibitors of the enzyme block the development of phosphorylated tau deposits (Bi et al, 2000). Third, metabolism within lysosomes generates products necessary for proper functioning of the endoplasmic reticulum, the loss of which can impair calcium buffering (Jmoudiak and Futerman, 2005). This would have a diverse array of effects including activation of the calcium-sensitive protease calpain (Fig.…”
Section: Relationship Of Plasticity Deficits To Generalized Brain Agingmentioning
confidence: 99%
“…Similarly, in the neuronal models of GD, it was shown that GlcCer directly activated phospholipid synthesis by activation of CTP:phosphocholine cytidylyltransferase (CCT), which was shifted from cytosol to the endoplasmic reticulum (Bodennec et al 2002;Korkotian et al 1999;Pelled et al 2005). All these phenomena could be explained by the transfer of the uncleaved lysosomal GlcCer into the neuronal endoplasmic reticulum (Bodennec et al 2002;Jmoudiak and Futerman 2005). The role of GlcSph in neuronal degeneration is mentioned below.…”
Section: Glucosylceramide Transfermentioning
confidence: 99%
“…The deficient activity of this enzyme results in the accumulation of glucosylceramide (GlcCer) within the lysosomes. Type I (GD1) is the most common form of GD and may imply a large variety of symptoms, ranging from completely asymptomatic to child-onset forms (Beutler and Grabowski 2001;Jmoudiak and Futerman 2005).…”
Section: Introductionmentioning
confidence: 99%